Relationship between uric acid/ albumin ratio and coronary slow flow - Demirkıran, Aykut; Aydın, Cihan (The European Research Journal, 2023)
Objectives: Although the pathophysiology of coronary slow flow is not fully understood, evidence suggesting endothelial dysfunction and subclinical widespread atherosclerosis in genesis has grown in recent years. Our aim in this study is to investigate the relationship between uric acid/ albumin ratio and coronary slow flow. Methods: One hundred and five coronary slow flow patients (determined by the Thrombolysis in Myocardial Infarction-frame count method) and one-hundred patients with normal coronary low were included retrospectively. The uric acid/ albumin ratio was investigated in all patients participating. Results: In the logistic regression analysis, it was revealed that high uric acid levels, uric acid/ albumin ratios, and male gender were independent predictors for coronary slow flow. Among these parameters, the uric acid/ albumin ratio was the best predictor of coronary slow flow. Based on the receiver operating characteristics (ROC) analysis, the cut-off value of uric acid/ albumin ratio ≥ 0.57 was found to predict coronary slow flow with 68.3% sensitivity and 68.7% specificity. In multivariate logistic regression analysis, high uric acid levels (OR: 2.22; 95% CI (1.551-3.200), p < 0.001), high serum uric acid/ albumin ratio (OR: 37.7 95% CI (8.176-234.387), p < 0.001), male gender (OR: 0.157; 95% CI (0.078-0.318), p < 0.001) were independent predictors of coronary slow flow. Conclusions: High uric acid/ albumin ratio was detected as an independent predictor for coronary slow flow. Larger studies are needed to elucidate its role in the pathophysiology of coronary slow flow.